2020
DOI: 10.3389/fneur.2019.01418
|View full text |Cite
|
Sign up to set email alerts
|

The Role of NLRP3 and IL-1β in Refractory Epilepsy Brain Injury

Abstract: The objective of this study was to investigate the roles and mechanisms of inflammatory mediators NLRP3 and IL-1β in refractory temporal epilepsy brain injury. Method: First, the brain tissue and the peripheral blood of children undergoing intractable temporal lobe epilepsy surgery were analyzed as research objects. The expression levels of NLRP3 in brain tissue and IL-1β in blood were measured. A model of temporal lobe epilepsy was established using wild-type and NLRP3 knockout 129 mice. Pilocarpine was injec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
29
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 32 publications
5
29
1
2
Order By: Relevance
“…Both DLB and control groups had AI values suggesting rightward asymmetry, while the DLB group had higher absolute AI values than the control group (Table 1 ). These results are consistent with Chen’s previous study showing that DLB patients have significantly higher absolute AI values than controls, along with significant rightward asymmetry in terms of local and global network efficiency 31 . However, the controls in the previous study had no asymmetry in terms of global and local network efficiency, while our control group had significant rightward metabolic asymmetry.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Both DLB and control groups had AI values suggesting rightward asymmetry, while the DLB group had higher absolute AI values than the control group (Table 1 ). These results are consistent with Chen’s previous study showing that DLB patients have significantly higher absolute AI values than controls, along with significant rightward asymmetry in terms of local and global network efficiency 31 . However, the controls in the previous study had no asymmetry in terms of global and local network efficiency, while our control group had significant rightward metabolic asymmetry.…”
Section: Discussionsupporting
confidence: 93%
“…Different methodology of network analysis in the previous study could be a reason for the different laterality in our control subjects. Although the previous study showed that PD dementia (leftward asymmetry) and DLB (rightward asymmetry) patients had different asymmetric patterns in local efficiency 31 , more frequent mixed AD pathology in the DLB group than in the PD dementia group could have contributed to the different laterality 32 . Also, an increased absolute AI was shown to be characteristic of PD dementia, as well as DLB, in the previous study 31 , and PC1 well explained the increased absolute AI in our DLB patients (Supplementary Table 4 ).…”
Section: Discussionmentioning
confidence: 76%
“…Semaglutide decreases inflammatory cytokine secretion in PTZ-kindled mice. In various respects, inflammasome activation contributes to the release of inflammatory cytokines, which play a pivotal role in epileptogenesis (14,15,38). The present study demonstrated that semaglutide blocked NLRP3 inflammasome activation.…”
Section: Semaglutide Decreases Hippocampal Neuron Apoptosis In Ptz Kindled-micesupporting
confidence: 60%
“…The NLRP3 inflammasome results from the assembly of NLR family pyrin domain containing 3 (NLRP3), apoptosis-associated speck-like protein (ASC) and caspase-1 (14), and promotes the secretion of inflammatory cytokines, influencing the pathophysiology of epilepsy (14). Additionally, in animal and clinical epilepsy-related research, increased levels of the NLRP3 inflammasome and neuroinflammatory cytokines have been detected in hippocampal tissues (15,16), suggesting their close association with epileptogenesis. Moreover, numerous studies have reported that inhibiting NLRP3 activation and inflammatory cytokine secretion decreases to occurrence of epileptic seizures and ameliorates cognitive dysfunction (17,18).…”
Section: Semaglutide Attenuates Seizure Severity and Ameliorates Cognitive Dysfunction By Blocking The Nlr Family Pyrin Domain Containingmentioning
confidence: 99%
“…One to three milliliters of whole blood were drawn by peripheral venipuncture into a K 2 -EDTA vacutainer tube. Plasma collection was selected to optimize yield of cytokines of interest in epilepsy, in particular those within the IL-1 family and NLRP3 inflammasome signaling pathways including IL-1β and IL-6 ( de Jager et al., 2009 ; Ulusoy et al., 2020 ; Wu et al., 2019 ). Within one hour of collection ( Henno et al., 2017 ), blood was centrifuged for 10 minutes at 1,300 g at 4°C, the supernatant transferred to a separate tube, and then centrifuged for 10 minutes at 16,000 g at 4°C.…”
Section: Methodsmentioning
confidence: 99%